When the allergy alarm bells toll: The role of Toll-like receptors in allergic diseases and treatment - Wenger, Mario; Grosse-Kathoefer, Sophie; Kraiem, Amin; Pelamatti, Erica; Nunes, Natalia; Pointner, Lisa; Aglas, Lorenz (Frontiers in Molecular Biosciences, 2023)
Toll-like receptors (TLRs) of the human immune system are specialized pathogen detectors able to link innate and adaptive immune responses. TLR ligands include among others bacteria-, mycoplasmaor virus-derived compounds such as lipids, lipo-and glycoproteins and nucleic acids.Not only are genetic variations in TLR-related genes associated with the pathogenesis of allergic diseases, including asthma and allergic rhinitis, their expression also differs between allergic and nonallergic individuals. Due to a complex interplay of genes, environmental factors, and allergen sources the interpretation of TLRs involved in immunoglobulin E-mediated diseases remains challenging.Therefore, it is imperative to dissect the role of TLRs in allergies.In this review, we discuss (i) the expression of TLRs in organs and cell types involved in the allergic immune response, (ii) their involvement in modulating allergy-associated or -protective immune responses, and (iii) how differential activation of TLRs by environmental factors, such as microbial, viral or air pollutant exposure, results in allergy development. However, we focus on (iv) allergen sources interacting with TLRs, and (v) how targeting TLRs could be employed in novel therapeutic strategies. Understanding the contributions of TLRs to allergy development allow the identification of knowledge gaps, provide guidance for ongoing research efforts, and built the foundation for future exploitation of TLRs in vaccine design.